2019
DOI: 10.1007/s11769-019-1083-6
|View full text |Cite
|
Sign up to set email alerts
|

A Macroinvertebrate Multimetric Index for the Bioassessment of Wetlands Adjacent to Agriculture Fields in the Sanjiang Plain, China

Abstract: Adjacent intensive agriculture disturbs the natural condition of wetlands. However, to assess the effect of this agriculture on wetlands, few studies have used indices based on aquatic invertebrates. Multi-metric indices (MMIs) have been successfully used to assess freshwater ecosystems worldwide and are an important management tool, but little is known about their applicability in the Sanjiang Plain, Northeast China. In this study, we developed a MMIs for aquatic invertebrates to assess freshwater wetlands in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…In those cases, still, wetlands that are of the best possible condition should be used for reference, although other factors must be taken into consideration as well, such as wetland type and proximity. For example, Wu et al ( 2019 ), studying wetlands in the Sanjiang Plain in China, sampled “27 wetlands across a range of conditions, from reference wetlands in Natural Reserves to those affected by adjacent, intensive agriculture in the Sanjiang Plain, China”. That choice of reference wetlands implies that wetlands in reserves are of better condition than wetlands within the same ecoregion that are adjacent to agricultural activities.…”
Section: Reference Wetlands In Highly Altered Landscapesmentioning
confidence: 99%
“…In those cases, still, wetlands that are of the best possible condition should be used for reference, although other factors must be taken into consideration as well, such as wetland type and proximity. For example, Wu et al ( 2019 ), studying wetlands in the Sanjiang Plain in China, sampled “27 wetlands across a range of conditions, from reference wetlands in Natural Reserves to those affected by adjacent, intensive agriculture in the Sanjiang Plain, China”. That choice of reference wetlands implies that wetlands in reserves are of better condition than wetlands within the same ecoregion that are adjacent to agricultural activities.…”
Section: Reference Wetlands In Highly Altered Landscapesmentioning
confidence: 99%
“…The total number of taxa was one of the six core metrics chosen for the development of our MMI. The metric taxa richness was widely selected as a core metric by the previous studies (Mereta et al, 2013;Melo et al, 2015;Lu et al, 2019;Wu et al, 2019) as well because of its ability to separate impaired wetlands from reference wetlands. Barbour et al (1996) reported that a high taxonomic richness implies a better status of aquatic ecosystem conditions and the existence of adequate food resources availability for many species in aquatic ecosystems As it was previous results (Burton et al, 1999;USEPA, 2002;Menetrey et al, 2011;Lunde and Resh, 2012;Melo et al, 2015), we found the decreasing trend total number of taxa with increasing anthropogenic impacts such as hydrological modification and upstream agricultural activities, This suggested the poorer status of wetland ecosystem conditions in the impaired sites of our study wetlands than the ecosystem conditions in the reference sites.…”
Section: Discussionmentioning
confidence: 99%
“…Another core metric that was selected for the construction of the MMI was Margalef's Index. Margalef's Index has not been commonly used to develop MMI for the assessment of ecological conditions and water quality of wetlands (Kashian and Burton, 2000;Haugerud, 2003;Lunde and Resh, 2012;Mereta et al, 2013;Melo et al, 2015;Lu et al, 2019;Wu et al, 2019). It has been selected as a core metric by the studies (Nguyen et al, 2014;Odabaşı et al, 2022), which were conducted for streams' water quality or ecological health assessment.…”
Section: Discussionmentioning
confidence: 99%
“…While vegetation recovery can take decades (Taddeo & Dronova 2018), necessitating the need for long‐term studies (Joosten et al 2016; Hancock et al 2018), some studies show that aquatic invertebrates are effective early indicators of the success of habitat restoration projects (Jahnig et al 2010; Li et al 2015). Aquatic invertebrates are important components of wetland ecosystems (Culler et al 2014; Wu et al 2019 a , 2019 b ) and can provide an accurate yet rapid indication of habitat response to disturbance (Yang et al 2017) because of their relatively quick generation time compared to animals like birds or fish. In addition, because of their relatively sedentary life (Brown et al 2009; Sartori et al 2015), aquatic invertebrates may be particularly good surrogates for comparing ecosystem function in restored, impaired, and natural wetlands (Balcombe et al 2005; Ruhí & Batzer 2014; Swartz et al 2019).…”
Section: Introductionmentioning
confidence: 99%